PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA XI (PERSERO) PABRIK GULA "PAGOTTAN" MADIUN - Devi Isma Wulayanti (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This research  have  a purpose  to study  about  influence  of discipline  work  to employees  performance,   Discipline  represent  one of factor  influencing   employees  performance.  With existence  of good discipline  a employees  will hold responsible  it's work and work  will be finished  effectively  and  is efficient.  Determination   of sampel  in this research use saturated  sampel that is all employees  part of Adrnisistrasi,  Public and Monetary on Sugar Mill "PAGOTTAN"  Madiun.  In this case researcher  only limiting to check employees  part of administration,   public  and monetary, because  of sugar mill only operating during the month of Juny until October. While  research  executed  during the month of Februari  until May. Hence,  felt researcher  will not be efficient  and effective  if checking part of production  and also parts  of related  to production  process.  Pursuant  to result of research  obtained  the level  of value  of rhitung  0,752  and rtabel  0,320,  on the other hand the level  of Sig(hitung) 0,000.  and Sig(prob)  0,05. Matter  this means  that value  of rcount  >= rtable (0,752 >= 0,320) or Sig(count) <= Sig(prob) (0,000 <= 0,05). While,  level  of R2 (R Square) 0,566.  Becoming,   contribution   influence  of Discipline  Work  to performance   equal  to 56,6%  while  the rest  equal  to 43,4%   influenced   by other  factor.  From  result  of test of F obtained   the  level  of value  of F(count) 46,973   and F(table) 4,113,  on the other  hand  the level  of Sig(count) 0,000  and  of  Sig(prob) 0,05  matter   this  means  that  value  of Fcount   >= Ftable (46,973  >= 4,113)   or  Sigcount   <= Sigprob(0,000   <= 0,05).  In  test  of  t can  be  made   line  of  regresi   the following   Y=  21,228   + 0,657X,   its meaning   if discipline   improved   once  will  happened increaseof employees   performance    counted   0,6570/0, if the other  factor  remain  to.  Level of value   of t(count) 6,854  and ttable 1,688,  on the  other  hand  the  level  of  Sig(count) 0,000  and Sig(prob) 0,05,  matter  this means  that value  of tcount >= tlable (6,854  >= 1,688)  or Sig(count) < Sig(prob) (0,000  < 0,05).  On the basis  of correlation   test,  test  F and test  oft  can be concluded   that there  is influence  Discipline   Work to Performance   Employees   PT. Plantation Of Nusantara XI (Persero) Sugar Mill "PAGOTTAN"    Madiun.